Galloping triboelectric nanogenerator for energy harvesting under low wind speed. (April 2020) - Zhang, Lanbin; Meng, Bo; Xia, Yang; Deng, Zhaoming; Dai, Huliang; Hagedorn, Peter; Peng, Zhengchun; Wang, Lin
Abstract: Energy harvesting technology of converting wind energy into available electricity is of great significance. Yet efficiently extracting wind energy at low wind speed still needs to be improved. A gaslloping triboelectric nanogenerator (GTENG) based on contact electrification between two flexible beams is proposed, resulting in a significant advancement of the TENG's performance under low wind speeds. The impact behavior occurs between a main beam attached with a bluff body subjected to cross flows and an auxiliary beam in the case of beyond critical wind speed. The coupled interaction between the two beams is investigated, and different contact modes have been observed. A theoretical model is constructed to further understand the working mechanism and oscillating behaviors of the GTENG. The GTENG with a 3 cm × 3 cm TENG cell achieves an output voltage of over 200V at a low wind speed of 1.4 m/s. In addition, it is meaningful that the average output power at 1.4 m/s reaches 60% of that at a relatively high wind speed of 6 m/s, which demonstrates the high output efficiency of GTENG under low wind speed. The nanogenerator's environmental adaptability is unveiled at an air-conditioner vent, indicating that the GTENG is promising to drive electric devices in outdoor environments. Graphical abstract: Image 1 Highlights: A novel galloping triboelectric nanogenerator is proposed for harvesting energy at low wind speed. A coupled dynamic model is developed and validated to characterize the harvester's performance. A jumping phenomenon is discovered to substantiate high output efficiency of the harvester at low wind speed. Single- and double-contact modes are identified for the harvester in different configurations.